ผลของหัวเชื้อสปอร์ราเอคโตไมคอร์ไรซา Russula spp. ต่อการกระตุ้นการเติบโตของกล้าไม้รัง Shorea siamensis Miq. - เชาวณี อ้นลำพูน (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
Trees of the family Dipterocarpaceae are the most important and dominant trees in the tropical forests of Southeast Asia as they play an important ecological role and are also important economically. In this study, an experiment was conducted to determine effects of spore inocula of ectomycorrhizal fungi, Russula rosea Pers., Russula virescens Fr.and Russula densifolia (Secr.) Gill. on growth stimulation of Shorea siamensis Miq. seedlings. Spores of the tested ectomycprrhizal fungi preserved in sand or in plastic bags at 4 ° C and room temperature was unable germination in sterile distilled water within 48 hours. The tested ectomycorrhizal spores could not germinate and form ectomycorrhizae with S. siamensis seedlings. Seedlings of S. siamensis were inoculated with spores of three ectomycorrhizal fungi and were grown in pots containing sterilized growing medium for 12 months. The results showed that the seedlings inoculated with spore inocula of R. rosea, R. densifolia and R. virescens had shoot height, stem diameter shoot and root dry weight total biomass and percentage of ectomycorrhizal colonization were significantly greater than non-inoculated seedlings. Inoculation with these ectomycorrhizal species had no significant effect of shoot N, P and K concentrations in the seedlings. The ectomycorrhizal roots of contaminant ectomycorrhizal fungi such as Tomentella spp. and Inocybe sp. were observed whereas ectomycorrhizal roots of the tested ectomycorrhizal fungi were not found. In addition, Survival rates of S. siamensis were greater for inoculated seedlings with spore concentration 107 spores per milliliter than non-inoculated seedlings at month 2 after the floods. The results suggest that inoculation with ectomycorrhizal fungi can stimulate the early growth and survival rates of S. siamensis seedlings.